The Effect of Sufi Breath and Meditation on Quantitative EEG: Is There a Difference? - Can Aren, Ebru; Tarlacı, Sultan (Journal of NeuroPhilosophy, 2022)
In this paper, we present a case study with quantitative EEG (QEEG) data to examine the neurophysiological effects of a specific breathing and meditation practice rooted in the Sufi esoteric practices of the Islamic tradition. The practice includes several coordinated cognitive activities. To evaluate the effects of the chosen breath and meditation practice, we compared the functional states of the brain in five frequency (from delta to gamma) bands before and after the completion of a 10-week practice. Statistically significant differences were found particularly in coherence and absolute power scores which are recorded during a no-task state. The increased synchronization and coherence within and between brain regions suggest that changes may be associated with negative entropy quality of spiritual energies. Conversely, the positive entropy has proven to be basis of many mental and physical disorders such as depression. This brain exercise helps permanently reshape the functional connectivity in the brain in a more neurologically conducive way.